2020
DOI: 10.3390/ijerph17239104
|View full text |Cite
|
Sign up to set email alerts
|

Buccal Bone Changes Around First Permanent Molars and Second Primary Molars after Maxillary Expansion with a Low Compliance Ni–Ti Leaf Spring Expander

Abstract: Background: Vestibular bone thickness changes and dento-alveolar buccal tipping of second primary molars and of first molars after maxillary expansion performed with a slow maxillary expansion protocol was investigated. Methods: Twenty patients (mean age 7.3 ± 0.9 years old; 9 male and 11 female) were treated according to the Leaf Expander protocol. Buccal alveolar bone thickness (BT), buccal alveolar bone height (BH), inter-dental angle (TIP), and inter-molar width (IW) regarding first molars and second prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
1
17
1
Order By: Relevance
“…These findings are in accordance with Habeeb et al and Cerruto et al, who demonstrated a significant posterior movement of the upper incisors following RME therapy. This effect is probably due to the deciduous anchorage that permits an anterior positioning of the screw compared with appliances cemented on the first permanent molar, as already reported in previous research [32,33]. Nevertheless, no significant difference was found between the three groups.…”
Section: Discussionsupporting
confidence: 54%
“…These findings are in accordance with Habeeb et al and Cerruto et al, who demonstrated a significant posterior movement of the upper incisors following RME therapy. This effect is probably due to the deciduous anchorage that permits an anterior positioning of the screw compared with appliances cemented on the first permanent molar, as already reported in previous research [32,33]. Nevertheless, no significant difference was found between the three groups.…”
Section: Discussionsupporting
confidence: 54%
“…If the clinician does not properly diagnose a patient’s skeletal problems and simply performs orthodontic treatment to improve the dentition, the patient’s fascial profile may worsen. Therefore, it is first necessary to accurately diagnose a patient’s problem using various diagnostic clinical data [ 2 , 3 ]. Whether orthognathic surgery is necessary or a compromise orthodontic treatment is feasible is an important issue for dental patients who visit a hospital for treatment [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, first maxillary permanent molars or second maxillary temporary molars are used for anchorage of the maxillary expander. The expander can be activated by discontinuous forces according to a rapid or slow protocol or by continuous forces via a pre-activated Ni-Ti expander [ 17 , 18 ]. The skeletal expansion of the midpalatal suture is possibly due to the hyalinization of the periodontal ligament of the anchored teeth and the transmission of the forces to the maxilla [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%